Academic Resilience Among Deaf Learners During E-Learning in the COVID-19 Era - Olufemi Timothy Adigun; Ntokozo Dennis Ndwandwe (Research in Social Sciences and Technology, 2022)
This study aimed to assess the contributory roles of parental involvement (PI), parental acceptance/rejection (PAR), academic self-efficacy (ASE), computer user self-efficacy (CUSE) vis-à-vis gender and the onset of deafness on the academic resilience (AR) of deaf learners who participated in e-learning during the pandemic. The Bioecological Systems Theory provided a framework for the study. Data was collected using a structured questionnaire from 292 (Male: n = 164; Female: n = 128; Mage = 16.5) deaf learners from 3 provinces in South Africa. Data generated was analysed with IBM SPSS 22 and IBM AMOS 26.0 packages. All the fit measures of the SEM fell within the acceptable range (χ2 = 69.15, df = 28, χ2/df = 2.46, IFI = 0.91, CFI = 0.94, GFI = 0.93, NFI = 0.96, and RMSEA = 0.062). According to the findings, PAR, ASE and CUSE had a directly significant relationship on the AR of deaf learners who participated in e-learning during the lockdowns. An indirect significant relationship was observed between the latent variables and academic resilience when observed through the onset of deafness. Based on the findings, appropriate recommendations were made.